ChemInform Abstract: Catalytic Asymmetric Synthesis of Enantioenriched β‐Nitronitrile Bearing a C‐CF3 Stereogenic Center. Issue 31 (14th July 2016) - Jakhar, Ajay; Kumari, Prathibha; Nazish, Mohd; Khan, Noor‐ul H.; Kureshy, Rukhsana I.; Abdi, Sayed H. R.; Suresh, E.
Abstract: by hydrocyanation reaction using an in situ generated chiral Ti(IV) salen complex as catalyst